Detection of CO2 using a quartz-crystal microbalance - GOMES, MT
Several amines have been evaluated with respect to stability, sensitivity and reversibility, regarding the analysis of carbon dioxide. The sensitivity of the amines has been related to their molecular structure and reactivity, and THEED was shown to be the best choice. However, 1,2-diaminoethane, 1,3-diaminopropane and 1,2-diaminopropane can be used, at least at 1 degrees C, with a smaller sensitivity and for shorter periods.